Online Determinants of E-Customer Satisfaction: Application to Website Purchases in Tourism - Pereira, H.; Salgueiro, M.F.; Rita, P. (International Network of Business and Management Journals, 2014)
This paper investigates the influence of four variables on online tourism customer satisfaction – website image perceptions, online routine, online knowledge, and customer innovativeness -, allowing for their simultaneous effects. The moderator role of three socio-demographic characteristics – gender, age group and educational background – is discussed. A questionnaire was applied to a sample of 3188 regular online buyers of the national leader in the tourism sector. The statistical analyses were conducted within the Structural Equation Modeling framework. The most important results have shown that there are three determinants that significantly influence e-customer satisfaction – website image, routine and knowledge. Only gender has indeed a moderator role regarding the impact of website knowledge on e-satisfaction. These results allow a better understanding of customer specificities, with practical actions being aimed at their real needs and expectations.